THE FORMATION OF A PERSONAL AND NATIONAL IDENTITY ON THE EXAMPLE OF SPORTS PHOTOGRAPHY AS A SYMBOLIC CAPITAL - ANGELOVA-IGOVA, B; BORISSOVA, S; YAKOVLEVA, L.S; KUDASHOV, V.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The article is devoted to the study of personal and national identities on the example of sports photos as a symbolic capital. The purpose of this study is to show how photography and sports come together, in a way that together contributes to the consolidation of the nation, contributes to national pride and identity, and hence - to forming personal identity on the base of them either. The structural-functional approach is used, in particular, the theory of "social action" by the American philosopher J. G. Mead. Photography is the channel through which the most international language such as sports can be transmitted, and the individual experience by it unified and integrated in the process of forming personal identity. Of particular interest are the photographs of athletes in Europe and how they contribute to the accumulation of symbolic capital for nation-states, and for self-determination of personal identity. The authors note that photography is an important part of people's daily lives, and its significance goes beyond their nature to entertain. A photographic image provides the basis for identification. A person through a visual image seeks to determine his personal, and then national identity. In today's world, identity is a dynamic system. In this regard, it can be compared with sports, which also constantly develop and ultimately open up new sports, modify qualification competitions, etc. Another social field that is on the rise at the same time is professional sports. By the mid-20th century, the sport of the privilege of the rich was becoming a mass sport. It was not until the 20th century that workers, women and minority groups had access to sports. The authors conclude that in the context of the importance of interdisciplinary research, which allows revealing the processes of formation of national and personal identity, research of this nature can take on further development.